A8.19 Non-lymphoid CD103+ dendritic cells are required for the initiation of collagen-induced arthritis. (31st January 2014) - Ramos, M I; Garcia, S; Baum, W; Helder, B; Aarrass, S; Reedquist, K A; Schett, G; Tak, P P; Lebre, M C
Abstract : Background and Objectives: Dendritic cells (DCs) are essential for the initiation of synovial inflammation, but it is unclear which subset of DCs performs this task. We have shown that FMS-like tyrosine kinase 3 ligand (Flt3L)-dependent DCs are important for disease development in a mouse model for RA. However since Flt3L-/- mice have reductions in all conventional (c)DCs it remained unclear which subset is required for disease induction. Materials and Methods: CIA was induced in Flt3L-/-, Batf3-/- (mice lacking both CD103 + and CD8a + DCs) and WT C57/BL6 littermates. In vitro and in vivo uptake and migration was performed using bone marrow (BM)-DCs and dermal DCs. Antigen presentation was studied in vivo by adoptive transfer of CFSE-labeled OT-I or OT-II T cells + OVA in Flt3L-/- and WT mice and in vitro by culturing BM-DCs with OT-I and OT-II cells. T cell proliferation was analysed by CFSE dilution. To study BM-DC function qPCR array (Dendritic and Antigen Presenting Cell PCR Array- Qiagen) for 84 genes was performed. To test the potential of a Flt3 inhibitor (CEP701) in the prevention of CIA, an in vivo study was performed injecting CEP701 before the onset of disease in DBA-1 mice. Results: Flt3L-/- mice were susceptible to innate K/BxN arthritic model and arthritic T cell transfer. Batf3-/- mice lacking both CD103 + and CD8a + DCs were resistant to CIA, demonstrating that CD11b + and monocyte-derived DCs (moDCs) were not sufficient to induce CIA. The amount of DCs carrying antigen reaching the LN in Flt3L-/- mice was reduced compared with WT. Uptake and migratory capacity was similar in Flt3L-/- BM-DCs compared to WT BM-DCs. CEP701 (a Flt3L inhibitor) treatment prevented CIA induction, and reduced dramatically CD103 + DCs in the lymph nodes and synovium. Human CD141hi DCs, homologues of mouse CD103 + DCs, were present and increased in inflamed rheumatoid arthritis (RA) synovium. Conclusions: Antigen presentation in Flt3L-/- mice is impaired. As CD103 + DCs are absent in Flt3L-/- mice and are important in (cross)-presenting antigens our data reveals a crucial role for CD103 + DCs in the induction of CIA. As a consequence of CD103 + DC absence Flt3L-/- mice showed a reduction in T cell activation in particularly reduced CD8 T cell responses. Hence this study identified non-lymphoid CD103 + DCs as the main subset orchestrating the initiation of cell-mediated immunity in arthritis. Targeting this DC subset might be of interest in individuals at risk of developing autoimmune disorders.